2001. Susceptibility of Aerococcus urinae to Fluoroquinolones: Broth Microdilution and Gradient Diffusion. (26th November 2018) - Berteau, Tammy; Roy, France-Émilie; Bestman-Smith, Julie; Lapierre, Simon Grandjean; Longtin, Jean; Dufresne, Simon-Frédéric; Domingo, Marc Christian; Leduc, Jean-Michel
Abstract: Background: Aerococcus urinae is an emerging urinary pathogen frequently identified by MALDI-TOF. It is generally susceptible to β-lactams, however, its susceptibility pattern to fluoroquinolones (FQ) remains variable. The goals of this study were (i) to evaluate the performance of the gradient diffusion method (Etest ® ) to determine FQ resistance compared with broth microdilution (BMD) and (ii) to estimate the resistance rate of A. urinae toward FQ in Quebec hospitals. Methods: Two hundred seven consecutive isolates of A. urinae from urinary tract specimens originating from five hospitals in Quebec and Montreal were identified by MALDI-TOF (Vitek-MS and Bruker). All isolates were tested with the BMD and gradient diffusion methods. BMD was carried out in triplicate and was conducted in accordance with CLSI guidelines (M45-A3). Isolates with insufficient growth at 24 hours were reincubated and evaluated at 48 hours. The gradient diffusion method was carried out using Etest ® strips on MH agar with 5% sheep blood. Results: Of the 207 isolates of A. urinae, 52 (25%) gave uninterpretable results using the BMD method (insufficient growth = 20; trailing = 32). We obtained the following results for the remaining 155 isolates: BMD readings were often complicated by noticeably poor growth. The categorical agreement of the Etest ® was 83% for ciprofloxacin and 95% for levofloxacin. Four very major errors were identified in a preliminary manner on 11% (4/35) of the ciprofloxacin-resistant isolates and 11%(4/35) of the levofloxacin-resistant isolates. Agar dilution will be done to confirm these results. Conclusion: In our experience, the method recommended by the CLSI for A. urinae susceptibility testing of FQ presented several problems, including insufficient growth and difficult reading. The Etest ® appears to be a promising method for susceptibility testing of FQ for urinary tract isolates, but will first require a further comparison with agar dilution methods. In our study, the rate of FQ non-susceptibility of A. urinae was 27% for levofloxacin and 33% for ciprofloxacin. Therefore, FQ cannot be empirically recommended for the treatment of urinary tract infections caused by A. urinae . Disclosures: J. M. Leduc, Biomérieux: Investigator, Research grant.